Hubungan Beberapa Karakteristik Kanker Payudara Berdasarkan Kelompok Usia - Agatha MA Putri; Jayadi Tejo; Wiwiek Probowati; Jonathan W Siagian (Universitas Kristen Maranatha, 2022)
In 2020, Global Cancer Observatory reported breast cancer incidence was 11.7% and mortality was 6.9%, most presenting a late-stage and delaying diagnosis. The study aimed to assess the breast cancer clinicopathologic characteristics according to the age groups. The research was conducted on 98 Medical Records from Bethesda Hospital Yogyakarta. The variable data were analyzed by univariate and the association between variables were analyzed with binary logistic regression with odds ratio and 95% confidence interval. The presentation of age groups ≤ 30 years (1,02%), 31-40 years (12,24%), 41-50 years (25,51%), 51-60 years (46,94%), and ≥ 61 years (15,31%); right breast (48,98%) and left breast (51,02%); stage I (3,06%), II (28,57%), III (55,10%), dan IV (13,27%); ductal type of breast cancer (89,80%) and others (10,20%); molecular subtype luminal A (43,88%), luminal B (14,29%), HER-2 neu enriched (29,59%), and basal-like/triple-negative (12,24%). There wasn’t any association between age groups and stages (p=0.368). There was an association between age groups and molecular subtype (p=0.013, OR 2.993 CI95% 1.239-7.230). Conclusions: The commonest clinicopathologic characteristic of breast cancer patients were in the age group 51-60 years, left breast, high stage, ductal type, and luminal A. Hormone receptors in breast cancer expressed more common in patients ≤50 years.